Effect of Statin Therapy on Choroidal Structure in Patients with Hyperlipidemia: A Case–Control Study with Optical Coherence Tomography - Hepokur, Mustafa; Çebi, Aslıhan Yılmaz; Çelebi, Medine Güneş; Salı, Fatma; Çelik, Fatma Betül; Oğuz, Halit (Cerrahpaşa Medical Journal, 2023)
Objective: To investigate the impact of statin therapy on choroidal structure. Methods: A case–control study included otherwise healthy patients with hyperlipidemia. 12 patients with low-density lipoprotein (LDL) levels below 210 mg/dL were treated with lifestyle changes, while 12 patients with levels above 210 mg/dL were additionally treated with atorvastatin. Optical coherence tomography images were obtained in the third month. Results: Choroidal thinning in the temporal region was observed in the statin group (P = .031, P = .033, P = .029 at different measuring points). Total choroidal and luminal areas were thinner in the statin group (P = .046 and P = .049), while the choroidal vascularity index remained the same (P = .853). Conclusion: It is uncertain whether choroidal thinning is mediated by decreased LDL levels or by decreased inflammation and oxidative stress. It may be advantageous to investigate statins in the management of pachychoroid spectrum disorders or oxidative stress-related diseases such as age-related macular degeneration. Cite this article as: Hepokur M, Yılmaz Çebi A, Çelebi MG, Salı F, Çelik FB, Oğuz H. Effect of statin therapy on choroidal structure in patients with hyperlipidemia: A case–control study with optical coherence tomography. Cerrahpaşa Med J. 2023;47(3):313-317.